1990
DOI: 10.1111/j.1476-5381.1990.tb12716.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive inotropic effect of porcine left ventricular extract on canine ventricular muscle

Abstract: 1 We previously isolated an extract from porcine left ventricle that possessed digitalis-like properties such as inhibition of cardiac and kidney Na+, K+-ATPase, displacement of [3H]-ouabain from its binding sites and cross reactivity with digoxin antibodies. The extract also had a positive inotropic effect on the guinea-pig heart. 2 In the present study the positive inotropic response of the extract was characterized in canine right ventricular trabeculae. Maximum inotropic response (501 + 20%) was produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…This factor was characterized pharmacologically as an endogenous inotropic factor (EIF). We have also demonstrated that EIF, in spite of its positive inotropic effect on cardiac preparations, lacks digitalis-like cardiac toxicity (Navaratnam et al, 1990) and only weakly cross-reacted with digitoxin anti-serum (Khatter et al, 1991). More recently, after several steps of purification of the crude fraction Navaratnam et al, 1990;Khatter et al, 1991), we demonstrated that one of the possible mechanisms of the EIF inotropic effect may be an increased transmembrane calcium influx (Chen et al, 1993).…”
Section: Introductionmentioning
confidence: 65%
“…This factor was characterized pharmacologically as an endogenous inotropic factor (EIF). We have also demonstrated that EIF, in spite of its positive inotropic effect on cardiac preparations, lacks digitalis-like cardiac toxicity (Navaratnam et al, 1990) and only weakly cross-reacted with digitoxin anti-serum (Khatter et al, 1991). More recently, after several steps of purification of the crude fraction Navaratnam et al, 1990;Khatter et al, 1991), we demonstrated that one of the possible mechanisms of the EIF inotropic effect may be an increased transmembrane calcium influx (Chen et al, 1993).…”
Section: Introductionmentioning
confidence: 65%